2000
DOI: 10.1093/jnci/92.18.1472
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Insulin-Like Growth Factor Family in Cancer Development and Progression

Abstract: The insulin-like growth factors (IGFs) are mitogens that play a pivotal role in regulating cell proliferation, differentiation, and apoptosis. The effects of IGFs are mediated through the IGF-I receptor, which is also involved in cell transformation induced by tumor virus proteins and oncogene products. Six IGF-binding proteins (IGFBPs) can inhibit or enhance the actions of IGFs. These opposing effects are determined by the structures of the binding proteins. The effects of IGFBPs on IGFs are regulated in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
901
3
21

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,254 publications
(947 citation statements)
references
References 259 publications
22
901
3
21
Order By: Relevance
“…The insulin-like growth factor 1 receptor (IGF-1R), a tetrameric receptor tyrosine kinase (RTK), is important for transformation, proliferation of malignant cells (Baserga, 1995;Baserga et al, 1997;Adams et al, 2000;LeRoith and Roberts, 2003;Larsson et al, 2005), crucial for preventing apoptosis, maintaining malignant phenotype and for resistance to chemotherapy (Baserga, 1995(Baserga, , 2000Yu and Rohan, 2000;Samani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The insulin-like growth factor 1 receptor (IGF-1R), a tetrameric receptor tyrosine kinase (RTK), is important for transformation, proliferation of malignant cells (Baserga, 1995;Baserga et al, 1997;Adams et al, 2000;LeRoith and Roberts, 2003;Larsson et al, 2005), crucial for preventing apoptosis, maintaining malignant phenotype and for resistance to chemotherapy (Baserga, 1995(Baserga, , 2000Yu and Rohan, 2000;Samani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Both peptides activate growth-promoting signal transduction pathways by interacting with their receptors, and, to some extent, can also bind to their mutual receptors or to hybrid insulin/IGF-I receptors [9,10]. Other common effects include stimulation of sex steroid synthesis [41][42][43][44][45] and inhibition of SHBG production [24,26,46].…”
Section: Insulin and Igf-i: Correlations With Sex-steroid Hormone Conmentioning
confidence: 99%
“…In vitro studies have shown that insulin, IGF-I and sex-steroid hormones all promote cell growth and proliferation, and serum levels of these hormones have been associated with cancer risk [5,[9][10][11]. Evaluation of interrelationships between these hormones and their associations with adiposity may therefore provide information about the role of hormones in the association between excess weight and cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…6 In blood circulation, over 75% of IGF-I is bound to the insulin-like binding protein (IGFBP)-3. 7 Circulating IGF-I levels are largely determined by genetic factors and age, 8,9 and are also affected by sex, anthropometric indices, physical activity, exogenous sex hormones, smoking, alcohol consumption 10 and nutritional status. 6 Circulating levels of IGF-I and IGFBP-3 concentrations vary considerably between normal individuals, but blood levels in each individual are relatively constant.…”
Section: Introductionmentioning
confidence: 99%